2001
DOI: 10.2174/1381612013397591
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Chemokine Based Control of HIV Infection and Replication

Abstract: HIV infects and propagates into CD4+ T lymphocytes and macrophages, although many other cell types play an important role in virus spreading and pathogenesis. In addition to regulatory viral proteins, the cytokine network has early been implicated as a major controller of the plastic capacity of HIV to spread productively or rather remain silently integrated in the chromosomes of infected cells. The recent discovery of CCR5 and CXCR4 as essential entry co-receptors together with CD4 has highlighted a novel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 170 publications
1
20
0
Order By: Relevance
“…Indeed, transfection of a Tat-expressing plasmid (10,22,24) or incubation of U1 cells with exogenous Tat protein (25,26) rescues viral production. Minimal to undetectable levels of HIV are produced by unstimulated U1 cells, although robust virion release can be promptly induced in these cells upon stimulation with phorbol esters, such as PMA (27), and several proinflammatory cytokines (28,29). For this reason, this cell line has served as a useful model to identify cytokines and other factors capable of modulating HIV expression and replication in primary cells in vitro and ex vivo (28,30,31).…”
Section: U1 and U1-cr1 Chronically Infected Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, transfection of a Tat-expressing plasmid (10,22,24) or incubation of U1 cells with exogenous Tat protein (25,26) rescues viral production. Minimal to undetectable levels of HIV are produced by unstimulated U1 cells, although robust virion release can be promptly induced in these cells upon stimulation with phorbol esters, such as PMA (27), and several proinflammatory cytokines (28,29). For this reason, this cell line has served as a useful model to identify cytokines and other factors capable of modulating HIV expression and replication in primary cells in vitro and ex vivo (28,30,31).…”
Section: U1 and U1-cr1 Chronically Infected Cell Linesmentioning
confidence: 99%
“…Minimal to undetectable levels of HIV are produced by unstimulated U1 cells, although robust virion release can be promptly induced in these cells upon stimulation with phorbol esters, such as PMA (27), and several proinflammatory cytokines (28,29). For this reason, this cell line has served as a useful model to identify cytokines and other factors capable of modulating HIV expression and replication in primary cells in vitro and ex vivo (28,30,31). At the molecular level, in addition to Tat (32), several cellular transcription factors with binding sites in the HIV-1 long-terminal repeats (LTR) or present in the HIV genome (33) can be activated by chemical agents such as ionomycin (34) and PMA (35), superinfection by other viruses (36,37), or cytokine stimulation (28,29).…”
Section: U1 and U1-cr1 Chronically Infected Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the latter, cell surface expression of CD4 and chemokine receptors CCR5 (R5) and/or CXCR4 (X4) are required for HIV infection [4]. In addition, several cytokines favor HIV replication and HIV-associated diseases, and their expression is profoundly altered in the course of HIV infection towards a pro-inflammatory state [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, as we did not collect data on the ANA values of the patients, we cannot draw any definite conclusions. In other studies, researchers observed that when the viral load increased, numerous viral proteins antagonized chemokines by competitively binding their receptors, such as CCR5 and CXCR4 (35)(36)(37)(38). They suggested that levels of chemokines might be correspondingly downregulated (39).…”
Section: Discussionmentioning
confidence: 99%